Plasma Proteomic Profile Predicts Survival in Heart Failure With Reduced Ejection Fraction. (June 2021) - Gui, Hongsheng; She, Ruicong; Luzum, Jasmine; Li, Jia; Bryson, Timothy D.; Pinto, Yigal; Sabbah, Hani N.; Williams, L. Keoki; Lanfear, David E.
Abstract : Background: It remains unclear whether the plasma proteome adds value to established predictors in heart failure (HF) with reduced ejection fraction (HFrEF). We sought to derive and validate a plasma proteomic risk score (PRS) for survival in patients with HFrEF (HFrEF-PRS). Methods: Patients meeting Framingham criteria for HF with EF<50% were enrolled (N=1017) and plasma underwent SOMAscan profiling (4453 targets). Patients were randomly divided 2:1 into derivation and validation cohorts. The HFrEF-PRS was derived using Cox regression of all-cause mortality adjusted for clinical score and NT-proBNP (N-terminal pro-B-type natriuretic peptide), then was tested in the validation cohort. Risk stratification improvement was evaluated by C statistic, integrated discrimination index, continuous net reclassification index, and median improvement in risk score for 1-year and 3-year mortality. Results: Participants' mean age was 68 years, 48% identified as Black, 35% were female, and 296 deaths occurred. In derivation (n=681), 128 proteins associated with mortality, 8 comprising the optimized HFrEF-PRS. In validation (n=336) the HFrEF-PRS associated with mortality (hazard ratio, 2.27 [95% CI, 1.84–2.82], P =6.3×10 -14 ), Kaplan-Meier curves differed significantly between HFrEF-PRS quartiles ( P =2.2×10 -6 ), and it remained significant after adjustment for clinical score and NT-proBNP (hazard ratio, 1.37 [95% CI, 1.05–1.79], P =0.021). The HFrEF-PRS improved metrics of risk stratification (C statistic change, 0.009, P =0.612; integrated discrimination index, 0.041, P =0.010; net reclassification index=0.391, P =0.078; median improvement in risk score=0.039, P =0.016) and associated with cardiovascular death and HF phenotypes (eg, 6-minute walk distance, EF change). Most HFrEF-PRS proteins had little known connection to HFrEF. Conclusions: A plasma multiprotein score improved risk stratification in patients with HFrEF and identified novel candidates. Abstract : Supplemental Digital Content is available in the text.